2017
DOI: 10.25133/jpssv25n4.001
|View full text |Cite
|
Sign up to set email alerts
|

Internal Migration to the Southeast Region of Vietnam: Trend and Motivations

Abstract: Internal migration in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
0
0
2
Order By: Relevance
“…For those who have children, Table 3 shows that individuals who migrate subjectively will feel more adequacy in fulfilling the needs of their children, such as children's consumption, children's health, and children's education, compared to those who did not migrate (SW08, SW09, SW10, & SW11 has a positive result). This finding was the same as the research which found that migration and urbanization are positively related to child health (Jemiluyi, 2021), where health, education, and subjective well-being are the goals for migrants and their children in the destination area (Akdede & Giovanis, 2022;Ngoc et al, 2017). However, Akdede and Giovanis (2022) added that this positive impact on children did not apply to Southern European countries.…”
Section: Children's Needssupporting
confidence: 76%
“…For those who have children, Table 3 shows that individuals who migrate subjectively will feel more adequacy in fulfilling the needs of their children, such as children's consumption, children's health, and children's education, compared to those who did not migrate (SW08, SW09, SW10, & SW11 has a positive result). This finding was the same as the research which found that migration and urbanization are positively related to child health (Jemiluyi, 2021), where health, education, and subjective well-being are the goals for migrants and their children in the destination area (Akdede & Giovanis, 2022;Ngoc et al, 2017). However, Akdede and Giovanis (2022) added that this positive impact on children did not apply to Southern European countries.…”
Section: Children's Needssupporting
confidence: 76%
“…Yếu tố này bao gồm tiền lương thấp, tỷ lệ thất nghiệp cao, thiếu các yếu tố chăm sóc sức khỏe tại nơi đi, yếu tố chính trị (xung đột chính trị, sắc tộc, quốc gia), kinh tế, văn hóa (Lee, 1966), năng suất lao động thấp và tình trạng dư thừa lao động trong khu vực nông nghiệp (Lewis, 1954;Lee, 1966). Ngoài ra, do áp lực nợ nần của gia đình, hệ thống giáo dục và y tế nghèo nàn hay nói cách khác điều kiện sống tại nơi đi kém phát triển cũng như mong muốn đoàn tụ gia đình cũng là một trong những nhân tố "đẩy" người dân di cư (Lê Bạch Dương và Nguyễn Thanh Liêm, 2011;Ngoc et al, 2017). Cũng theo Ngoc et al (2017), mong muốn rời khỏi khu vực nông nghiệp và rời bỏ quê hương cùng với những thách thức của điều kiện sống và sản xuất dưới tác động của thảm họa thiên nhiên (Lee, (1966) gọi là lực đẩy tiềm năng từ hiểm họa thiên nhiên) cũng là một lực đẩy của di cư.…”
Section: Tổng Quan Nghiên Cứuunclassified
“…Ngoài ra, do áp lực nợ nần của gia đình, hệ thống giáo dục và y tế nghèo nàn hay nói cách khác điều kiện sống tại nơi đi kém phát triển cũng như mong muốn đoàn tụ gia đình cũng là một trong những nhân tố "đẩy" người dân di cư (Lê Bạch Dương và Nguyễn Thanh Liêm, 2011;Ngoc et al, 2017). Cũng theo Ngoc et al (2017), mong muốn rời khỏi khu vực nông nghiệp và rời bỏ quê hương cùng với những thách thức của điều kiện sống và sản xuất dưới tác động của thảm họa thiên nhiên (Lee, (1966) gọi là lực đẩy tiềm năng từ hiểm họa thiên nhiên) cũng là một lực đẩy của di cư. Trong khi đó các nhân tố kéo thường liên quan tới nơi đến của người di cư bao gồm sự chênh lệch mức lương kì vọng giữa khu vực nông thôn và thành thị (Harris and Todaro, 1970), cơ hội việc làm, chênh lệch mức sống và điều kiện sống, lối sống đô thị (mong ước được trở thành công dân đô thị, và thành phố hấp dẫn người di cư đặc biệt là người di cư trẻ tuổi ) (Lee, 1966;Ngoc et al, 2017), quá trình công nghiệp hóa, đô thị hóa (Lewis, 1954); mạng lưới xã hội của người di cư (Đặng Nguyên Anh, 1998); khả năng dễ dàng đăng kí hộ khẩu (Ngoc et al, 2017).…”
Section: Tổng Quan Nghiên Cứuunclassified